Harnessing biodiversity: the Malagasy Institute of Applied Research (IMRA) - Heys Jennifer; Masum Hassan; Puri Manveen; Singer Peter A (BMC, 2010)
Abstract Background Biopiracy - the use of a people's long-established medical knowledge without acknowledgement or compensation - has been a disturbing historical reality and exacerbates the global rich-poor divide. Bioprospecting, however, describes the commercialization of indigenous medicines in a manner acceptable to the local populace. Challenges facing bioprospectors seeking to develop traditional medicines in a quality-controlled manner include a lack of skilled labor and high-tech infrastructure, adapting Northern R&D protocols to Southern settings, keeping products affordable for the local population, and managing the threat of biopiracy. The Malagasy Institute of Applied Research (IMRA) has employed bioprospecting to develop new health treatments for conditions such as diabetes and burns. Because of its integration of Western science and Malagasy cultural traditions, IMRA may provide a useful example for African and other organizations interested in bioprospecting. Discussion IMRA's approach to drug development and commercialization was adapted from the outset to Malagasy culture and Southern economic landscapes. It achieved a balance between employing Northern R&D practices and following local cultural norms through four guiding principles. First, IMRA's researchers understood and respected local practices, and sought to use rather than resist them. Second, IMRA engaged the local community early in the drug development process, and ensured that local people had a stake in its success. Third, IMRA actively collaborated with local and international partners to increase its credibility and research capacity. Fourth, IMRA obtained foreign research funds targeting the "diseases of civilization" to cross-fund the development of drugs for conditions that affect the Malagasy population. These principles are illustrated in the development of IMRA products like Madeglucyl, a treatment for diabetes management that was developed from a traditional remedy. Summary By combining local and international research interests, IMRA has been able to keep its treatments affordable for the Malagasy population. Our analysis of IMRA's history, strategy, and challenges suggests that other developing world institutions seeking to use bioprospecting to address issues of local access to medicines would be well-advised to treat traditional medical knowledge with respect and humility, share its benefits with the local community, and pursue strategic partnerships.